New Cernotina Ross 1938 (Trichoptera: Polycentropodidae) from Serra do Divisor, Acre, Brazil - Pires, Marcos Adriano Ribeiro; Pes, Ana Maria; Camargos, Lucas M.; Hamada, Neusa (Zootaxa, 2024)
Two new species of the caddisfly genus Cernotina (Polycentropodidae) are described from the Parque Nacional da Serra do Divisor (PNSD), Acre, Brazil, Cernotina chicomendes sp. nov. and Cernotina divisor sp. nov. These two new species represent the first polycentropodids described from Acre State. Additionally, we update records for Cernotina hastilis Flint 1996 and Cernotina waorani Camargos, Ríos-Touma & Holzenthal 2017, including a distribution map for all the species mentioned here. We further emphasize the importance of protected areas for biodiversity conservation, especially the PNSD, which has recently faced threats due to a proposed road within its boundaries.